Genetic and clinical analysis in 10 Spanish patients with multiple endocrine neoplasia type 1 - Cebrián, Arancha; Herrera-Pombo, Jose Luis; Díez, Juan José; Sánchez-Vilar, Olga; Lara, Jose Ignacio; Vázquez, Clotilde; Picó, Antonio; Osorio, Ana; Martínez-Delgado, Beatriz; Benítez, Javier; Robledo, Mercedes (Springer Nature, 1999)
Multiple endocrine neoplasia type 1 (MEN 1) is characterised by the combination of tumours of the parathyroid, endocrine pancreas and anterior pituitary glands. In 1988 the MEN 1 gene was mapped to chromosome 11q13 and it was cloned in 1997. This gene contains 10 exons and extends across 9 Kb of genomic DNA; it encodes for a product of 610 amino acid named menin whose function is unknown. We have studied 10 unrelated MEN 1 kindreds by a complete sequencing analysis of the entire gene; mutations were identified in nine of them: five deletions, one insertion, two nonsense mutation and a complex alteration consisting of a deletion and an insertion that can be explained by a hairpin loop model. Two of the mutations have been previously described; the other seven were novel, and they were scattered throughout the coding sequence of the gene. As in previous series, no correlation was found between phenotype and genotype.